In vivo binding and retention of CD4-specific DARPin 57.2 in macaques. - Pavel Pugach; Anders Krarup; Agegnehu Gettie; Marcelo Kuroda; James Blanchard; Michael Piatak; Jeffrey D Lifson; Alexandra Trkola; Melissa Robbiani (PLoS ONE)
Background The recently described Designed Ankyrin Repeat Protein (DARPin) technology can produce highly selective ligands to a variety of biological targets at a low production cost. Methodology/principal findings To investigate the in vivo use of DARPins for future application to novel anti-HIV strategies, we identified potent CD4-specific DARPins that recognize rhesus CD4 and followed the fate of intravenously injected CD4-specific DARPin 57.2 in rhesus macaques. The human CD4-specific DARPin 57.2 bound macaque CD4(+) cells and exhibited potent inhibitory activity against SIV infection in vitro. DARPin 57.2 or the control E3_5 DARPin was injected into rhesus macaques and the fate of cell-free and cell-bound CD4-specific DARPin was evaluated. DARPin-bound CD4(+) cells were detected in the peripheral blood as early as 30 minutes after the injection, decreasing within 6 hours and being almost undetectable within 24 hours. The amount of DARPin bound was dependent on the amount of DARPin injected. CD4-specific DARPin was also detected on CD4(+) cells in the lymph nodes within 30 minutes, which persisted with similar kinetics to blood. More extensive analysis using blood revealed that DARPin 57.2 bound to all CD4(+) cell types (T cells, monocytes, dendritic cells) in vivo and in vitro with the amount of binding directly proportional to the amount of CD4 on the cell surface. Cell-free DARPins were also detected in the plasma, but were rapidly cleared from circulation. Conclusions/significance We demonstrated that the CD4-specific DARPin can rapidly and selectively bind its target cells in vivo, warranting further studies on possible clinical use of the DARPin technology.